2023
DOI: 10.1177/1098612x221145835
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden in cat owners: a cross-sectional observational study

Abstract: Objectives Caregiver burden has been found in owners of seriously ill pets; however, research to date has been heavily represented by dog owners. Prior caregiver burden work has neither intentionally focused on cat owners nor been appropriately powered to examine differences in owners of cats relative to owners of dogs. We expected that owners of an ill cat would exhibit greater caregiver burden than owners of a healthy cat but lower burden than owners of an ill dog. Methods A cross-sectional online assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In the current study, a statistical difference was observed between the degree of burden in cat caregivers (higher burden) compared to dog caregivers. Spitznagel et al [15] researched the occurrence of caregiver burden specifically in cat caregivers. It was observed that owners of sick cats had a higher burden than owners of a healthy cat, but a slightly lower burden than owners of sick dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, a statistical difference was observed between the degree of burden in cat caregivers (higher burden) compared to dog caregivers. Spitznagel et al [15] researched the occurrence of caregiver burden specifically in cat caregivers. It was observed that owners of sick cats had a higher burden than owners of a healthy cat, but a slightly lower burden than owners of sick dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on caregiver burden in cats are relatively scarce compared to those focusing on dogs. A recent study [15] added valuable insights by examining the caregiver burden of cat owners. The study hypothesized that owners of an ill cat would experience greater caregiver burden compared to owners of a healthy cat but lower burden than owners of an ill dog.…”
Section: Introductionmentioning
confidence: 99%
“…These findings demonstrate that A/H5N1 can eventually evolve into genotypes posing a threat to mammals, and this risk cannot be neglected, given the devastating outcomes such infections could have on human health (Abbasi, 2023). The risk of the introduction of A/H5N1 to the human population is particularly high when companion animals, such as cats, are affected because of close contact and the tendency of cat owners to increase caregiver burden when a cat becomes ill (Spitznagel et al, 2023). However, A/H5N1 infections in companion animals such as dogs and domestic cats have so far been very sporadic (Songserm et al, 2006a,b).…”
Section: A/h5n1 Infections In Catsmentioning
confidence: 95%
“…59,60 For cats, protective (negative) emotions associated with forceful administration of medications may cause stress and exacerbate the underlying condition; in patients with chronic pain, which are likely to be receiving multiple medications ('pill burden'), the issue is complicated further. For caregivers, the negative emotional, physical, financial and time impact of chronic conditions in the home care situation 61 -the 'caregiver burden' -requires recognition by, and support from, the veterinary team. Involving veterinary nurses/technicians in providing that support, including giving demonstrations on how to administer medication (Box 5), and following up with caregivers with open conversations on the challenges and successes they have encountered, can be highly beneficial.…”
Section: Medicating Catsmentioning
confidence: 99%